2013
DOI: 10.1177/0956797612464659
|View full text |Cite
|
Sign up to set email alerts
|

Would You Be Happier Living in a Greener Urban Area? A Fixed-Effects Analysis of Panel Data

Abstract: Urbanization is a potential threat to mental health and well-being. Cross-sectional evidence suggests that living closer to urban green spaces, such as parks, is associated with lower mental distress. However, earlier research was unable to control for time-invariant heterogeneity (e.g., personality) and focused on indicators of poor psychological health. The current research advances the field by using panel data from over 10,000 individuals to explore the relation between urban green space and well-being (in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
431
4
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 688 publications
(521 citation statements)
references
References 31 publications
(42 reference statements)
28
431
4
12
Order By: Relevance
“…These studies consistently find that living in an area with more green space is associated with less mental distress than living in an area with less green space. Moreover, in a longitudinal study that had over 10,000 U.K. residents (White et al, 2013), living in a greener urban area was associated with greater life satisfaction. Thus, it appears that having access to nature near one's home can provide a buffer against mental distress and promote a sense of satisfaction with one's life (cf.…”
Section: Nature and Hedonic Wellbeingmentioning
confidence: 96%
See 1 more Smart Citation
“…These studies consistently find that living in an area with more green space is associated with less mental distress than living in an area with less green space. Moreover, in a longitudinal study that had over 10,000 U.K. residents (White et al, 2013), living in a greener urban area was associated with greater life satisfaction. Thus, it appears that having access to nature near one's home can provide a buffer against mental distress and promote a sense of satisfaction with one's life (cf.…”
Section: Nature and Hedonic Wellbeingmentioning
confidence: 96%
“…A survey of 3,000 Finnish participants found that those who reported spending more of their leisure time engaged in nature-based recreational activities had higher emotional wellbeing than those who reported spending less of their free time in nature (Korpela, Borodulin, Neuvonen, Paronen, & Tyrväinen, 2014). A series of large-scale European studies based on data from national surveys has investigated the influence of nearby green space on wellbeing and mental health (de Vries, Verheij, Groenewegen, & Spreeuwenberg, 2003;Maas et al, 2009;Van den Berg et al, 2010;White, Alcock, Wheeler, & Depledge, 2013). These studies consistently find that living in an area with more green space is associated with less mental distress than living in an area with less green space.…”
Section: Nature and Hedonic Wellbeingmentioning
confidence: 99%
“…First, it can provide an attractive, visually appealing setting for housing, and the opportunity to express personal tastes and preferences (White et al, 2013). This setting also offers pleasant views from inside the home, leading to greater satisfaction with life.…”
Section: Introductionmentioning
confidence: 99%
“…Potentially healthful views should also be considered, such as those with the presence of flowers in different colors [40,41,44], aesthetically beautiful landscapes [44,45], places where the sea waves can be admired [40,43,46], streets with trees [47,48], the degree of naturalness of the landscape [12,45,49,50], views of agricultural landscape [45,51] and green spaces [13,45,49,50,52,53].…”
Section: Ecosystem's Health Potential (Ehp)mentioning
confidence: 99%